An assessment of the availability of water sources and hygiene practices in response to the Cholera outbreak in Harare City, Zimbabwe, 2018 - Tsitsi Juru; Tsitsi Kagodora; Christyna Tambanemoto; Tendai Chipendo; Tapiwa Dhliwayo; Memory Mapfumo; Arthur Kashiri; Notion Tafara Gombe; Gerald Shambira; Ruby Tapera; Mufuta Tshimanga (Journal of Interventional Epidemiology and Public Health)
Introduction: Cholera is an acute diarrheal disease that has a substantial impact on public health. Harare city reported the first cholera case on the 5th of September 2018, and by the 23rd of September 2018, 6403 cases and 43 deaths had been reported (case fatality rate 0.67%). Health promotion on hygiene practices was given through social media and door to door campaigns; however, cases continued to increase in the city. We therefore assessed the availability of water sources and hygiene practises in Harare city.